Structural basis of chemokine and receptor interactions: Key regulators of leukocyte recruitment in inflammatory responses. (24th October 2019) - Bhusal, Ram Prasad; Foster, Simon R.; Stone, Martin J.
Abstract: In response to infection or injury, the body mounts an inflammatory immune response in order to neutralize pathogens and promote tissue repair. The key effector cells for these responses are the leukocytes (white blood cells), which are specifically recruited to the site of injury. However, dysregulation of the inflammatory response, characterized by the excessive migration of leukocytes to the affected tissues, can also lead to chronic inflammatory diseases. Leukocyte recruitment is regulated by inflammatory mediators, including an important family of small secreted chemokines and their corresponding G protein‐coupled receptors expressed in leukocytes. Unsurprisingly, due to their central role in the leukocyte inflammatory response, chemokines and their receptors have been intensely investigated and represent attractive drug targets. Nonetheless, the full therapeutic potential of chemokine receptors has not been realized, largely due to the complexities in the chemokine system. The determination of chemokine–receptor structures in recent years has dramatically shaped our understanding of the molecular mechanisms that underpin chemokine signaling. In this review, we summarize the contemporary structural view of chemokine–receptor recognition, and describe the various binding modes of peptide and small‐molecule ligands to chemokine receptors. We also provide some perspectives on the implications of these data for future research and therapeutic development. Importance Statement: Given their central role in the leukocyte inflammatory response, chemokines and their receptors are considered as important regulators of physiology and viable therapeutic targets. In this review, we provide a summary of the current understanding of chemokine: chemokine–receptor interactions that have been gained from structural studies, as well as their implications for future drug discovery efforts.